Numerical study on the migration of drug carriers in capillaries with the immersed boundary-lattice Boltzmann method - Yulin Hou; Mengdan Hu; Dongke Sun; Yueming Sun (AIP Advances)
The study of drug delivery in the microcirculatory system has received widespread attention among researchers from different fields. In this study, a three-dimensional lattice Boltzmann method (LBM) coupled with the immersed boundary method (IBM) is applied to study the migration of cells and particles within capillaries. In this method, a multi-relaxation-time-LBM is employed to simulate the blood flow, and an energy model based on the finite element method is applied to calculate the particle dynamics. The fluid–particle interaction is solved using the IBM. The numerical model was validated and demonstrated great agreement with analytical solutions and previous studies. Drug carriers (DCs) with varying sizes and stiffness are considered in the simulation. Their impact on particles’ migration behaviors in straight capillaries is mainly explored. Results show that DC sizes have a significant impact on their motion trajectories and equilibrium regions. DCs of nanoscale exhibit excellent stability and uniform distribution during migration. The expansion of DC sizes increases their migration probability toward the vessel wall, resulting in greater motion confusion. Meanwhile, DCs of lower stiffness contribute to unstable trajectories and a significant increase in motion confusion, while their interactions with red blood cells (RBCs) are enhanced under conditions of high stiffness. DCs with moderate stiffness not only maintain stable motion but also exert minimal impact on the migration of RBCs. These findings afford valuable insights for the conception and design of DCs for biomedical applications.